Pontos de corte da relação cintura estatura e circunferência do pescoço em adolescentes: predição da obesidade, risco cardiovascular e relação com marcadores inflamatórios - CARVALHO, Wyllyane Rayana Chaves (2022)
INTRODUCTION: Obesity is an important factor for the increase of inflammatory cells and cardiovascular risk even in young populations. Indicators are being investigated, including the Waist-to-Height Ratio (WHtR) and Neck Circumference (CP) in the prediction of obesity, cardiovascular outcomes and the relationship with inflammatory markers in adolescence. OBJECTIVE: To identify the cut-off points for the waist-to- height ratio (WHtR) to determine obesity and its association with inflammatory markers in adolescents (Article 1) and to determine the cut-off points for CP and WHtR for predicting obesity and cardiovascular risk in adolescents (Article 2). METHODS: Cross- sectional study with 2209 adolescents aged 18 and 19 (Article 1), belonging to the third phase of the birth cohort held in São Luís 1997/1998, called “RPS”, carried out in 2016/2017; and a subsample of 648 adolescents from that cohort (Article 2). The total area under the ROC curve (AUC) was identified to assess the predictive capacity of RCEstand CP in relation to% GC, obtained by ADP and cardiovascular risk by PDAY. The association of CERs with Interleukin-6 (IL-6), tumor necrosis factor (TNF-α) and C- reactive protein (CRP) was evaluated. RESULTS: Article 1: Prevalence of obesity by %BF of 10.3% in males and 40.4% in females. The cutoff points of WHtR = 0.50 and AUC of 0.90 (95%CI 0.88-0.92) were identified for females and WHtR = 0.51 and AUC of 0.93 (95%CI 0.90 -0.97) for males. Elevated WHtR was associated with higher levels of IL-6 and CRP (p<0.05). Article 2: Prevalence of obesity of 7.6% in males and 41.3% in females and high risk by PDAY were from 13.8% and 10.9%, respectively. CP cutoff points identified for males=44.0, AUC was 0.70 (95%CI 0,58-0,83); WHtR=0.50, AUC 0.90 (95%CI 0.80-0.99). In females, PC=39.8, AUC was 0.75 (95%CI 0,69-0,80) and WHtR=0.50, AUC 0.87 (95%CI 0,83-0,90). To predict high cardiovascular risk in males, the AUC of CP was 0.71 (95%CI 0.62-0.80) and WHtR was 0.73 (95%CI 0.63-0.82); in females, the AUC of CP was 0.63 (95%CI 0.53-0.73) and WHtR was 0.55 (95%CI 0.45-0.65). CONCLUSION: The anthropometric indicators evaluated showed a statistically significant predictive capacity to identify obese individuals, in both sexes. Elevated WHtR values were associated with early inflammatory markers. For the prediction of cardiovascular risk, both indicators were classified as moderate, except for WHtR in females, considered to have low predictive capacity for risk. This study contributed to the identification of cutoff points of simple anthropometric indicators that can be used in health services to screen adolescents with obesity and high cardiovascular risk.